PERBANDINGAN KEMAMPUAN PEMECAHAN MASALAH FISIKA BERDASARKAN TEORI POLYA ANTARA KELAS XI MIA SMAN 7 DAN MAN 2 BULUKUMBA - Hidayat, Muhammad Yusuf; suarti, suarti; Rahma, Muftihatur (UIN Alauddin Makassar, 2023)
This research aims to determine physics problem solving abilities based on Polya theory for class XI MIA SMAN 7 Bulukumba, determine physics problem solving abilities based on Polya theory for class and MAN 2 Bulukumba. This type of research isAfter the factby designcausal comparison. The subjects in this research were class XI MIA SMAN 7 and MAN 2 Bulukumba. The instrument used is a problem solving ability test instrument based on the Polya indicator. The results of the descriptive analysis show that the average score for the physics problem solving ability of class XI MIA students at SMAN 7 Bulukumba is 63.88. Meanwhile, the average score for the physics problem solving ability of class XI MIA MAN 2 Bulukumba students is 74.36. Based on the average results obtained at SMAN 7 and MAN 2 Bulukumba, there is a difference between the ability to solve physics problems based on Polya theory for class XI MIA SMAN 7 and MAN 2 Bulukumba.